2016
DOI: 10.1016/j.jaci.2015.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Chediak-Higashi syndrome: Lysosomal trafficking regulator domains regulate exocytosis of lytic granules but not cytokine secretion by natural killer cells

Abstract: Background Mutations in LYST cause Chediak-Higashi syndrome (CHS), a rare immunodeficiency with impaired cytotoxic lymphocyte function, mainly that of natural killer (NK) cells. Our understanding of NK cell function deficiency in CHS, and how LYST regulates lytic granule exocytosis is very limited. Objective We sought to delineate cellular defects, associated with LYST mutations, responsible for the impaired NK cell function in CHS. Methods We analyzed NK cells from CHS patients with missense mutations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
64
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 57 publications
5
64
0
3
Order By: Relevance
“…In particular, several new publications have been focused on the biology of LYST, which when aberrant causes Chediak‐Higashi syndrome. These have demonstrated differences in the severity of disease associated with mutations that affect different domains of LYST . While lytic granules from patients with Chediak‐Higashi syndrome have previously been shown to be unusually large, this was recently advanced further for granules in NK cells from patients with LYST mutations .…”
Section: Primary Immune Deficiencies With Nk Cell Featuresmentioning
confidence: 97%
See 2 more Smart Citations
“…In particular, several new publications have been focused on the biology of LYST, which when aberrant causes Chediak‐Higashi syndrome. These have demonstrated differences in the severity of disease associated with mutations that affect different domains of LYST . While lytic granules from patients with Chediak‐Higashi syndrome have previously been shown to be unusually large, this was recently advanced further for granules in NK cells from patients with LYST mutations .…”
Section: Primary Immune Deficiencies With Nk Cell Featuresmentioning
confidence: 97%
“…These have demonstrated differences in the severity of disease associated with mutations that affect different domains of LYST . While lytic granules from patients with Chediak‐Higashi syndrome have previously been shown to be unusually large, this was recently advanced further for granules in NK cells from patients with LYST mutations . New studies have demonstrated that the size of lytic granules in Chediak‐Higashi syndrome patient NK cells can be a physical barrier to their directed secretion, as they are unable to transverse the cortical actin network located below the NK cell synaptic membrane .…”
Section: Primary Immune Deficiencies With Nk Cell Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…76 NK cells in CHS patients are hyperresponsive and hypersecretory but are unable to degranulate. 77,78 Although NK cell activation followed by granule convergence and polarization appears to be normal in LYST-deficient NK cells, the enlarged granules fail to pass through the cortical actin meshwork openings at the immunological synapse. 36 By monitoring granule size and granzyme B density prior to and following degranulation, we observed a selective loss of the pre-converged, large dense-core granules after degranulation.…”
Section: Trpml1-mediated Modulation Of Secretory Granules In Nk Cellsmentioning
confidence: 99%
“…Killing of K562 cells is dependent mainly on NKG2D (KLRK1) and LFA1 (ITGAL) receptors, whereas cytotoxicity toward 721.221 cells relies on 2B4 receptor expression by NK cells (Chen et al , 2007). The altered cytotoxicity toward target cells could be due to differences in expression of ligands for NK activating receptors by those target cells (Chen et al , 2006), and/or varied expression levels of activating receptors on NK cells (Gil-Krzewska et al , 2016). Nevertheless, cytotoxicity of HPS-2 NK cells did not improve with increased ratio of NK to target cells (data not shown), indicating a profound impairment of their cytolytic function, in agreement with previous reports (Enders et al , 2006; Jessen et al , 2013).…”
mentioning
confidence: 99%